Long term results after low dose ocular irradiation for choroidal haemangiomas - H Schilling; W. Sauerwein; Albrecht Lommatzsch; W. Friedrichs; S. Brylak; Norbert Bornfeld; A Wessing (1997)
The most common choice of treatment for choroidal haemangiomas (CH) in the past has been the employment of scatter photocoagulation of the surface. This management often requires repetitive treatment or additional invasive management due to massive exudative detachment of the retina. The aim of this retrospective study was to investigate the outcome of the alternative application of low dose external beam irradiation with high energetic photons on these tumours.A total absorbed dose of 20 Gy was applied to a total of 51 symptomatic eyes: 36 with a circumscribed CH of the posterior pole and 15 with diffuse CH as part of the Sturge-Weber syndrome. The indication for treatment was an exudative retinal detachment including or threatening the fovea. The mean follow up times in each group were 4.5 and 5.3 years, respectively. Out of a group of 33 patients from whom reliable data could be derived, 17 had symptoms lasting longer than 6 months.In 23 cases (63.8%) with circumscribed CH complete resolution of the subretinal fluid was achieved; the remaining 13 cases (36.2%) showed residual serous detachment distant to the fovea. The visual acuity improved by two or more lines in 14 cases (38.9%), remained stable in 14 cases (38.9%), and decreased in eight cases (22.2%). The functional success was dependent on the lag duration between onset of first subjective symptoms and treatment. The morphological results with diffuse CH were similar to those of the group of circumscribed CH. The visual acuity (VA) at last examination was improved in seven cases (46.6%); in the remaining eight cases, VA was unchanged or had deteriorated. The poor functional outcome in the latter was mainly attributable to secondary glaucoma.External beam irradiation is a useful and a low invasive therapeutic option for CH. A successful functional outcome is dependent on the time delay between first onset of symptoms and the beginning of therapy, the formation of subretinal fibrosis, and also on secondary glaucoma in the case of Sturge-Weber syndrome.